PENGOLAHAN ARSIP INAKTIF DI BIRO UMUM, HUMAS, DAN PROTOKOL SEKRETARIAT DAERAH DAERAH ISTIMEWA YOGYAKARTA - , TRI MERINA CHRISTIN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This graduating final report explained about managing inactive records in Biro Umum, Humas, and Protokol Sekretariat Daerah Daerah Istimewa Yogyakarta. The purpose of the report is to know inactive records in Sekretariat Daerah Daerah Istimewa Yogyakarta. This report use three methods. The methods complement each other that eventually result data and the right information. The three methods are observation, interview, and literature. The observation collected the data, direct practice of field works, and to know the reality of working. Moreover, the interview is direct dialogue with related parties and respondents. Furthemore, the literature is relevant with final report theme. The conclusion of this final report is managing inactive records in Biro Umum, Humas, and Protokol Sekretariat Daerah Daerah Istimewa Yogyakarta, the processing has been structured and appropnate with archival science procedure. The wonstraints faced is limited of human resourees and space